A Revitalization of Tandhakan Wedok Dance in Jatiguwi Village, Sumberpucung District, Malang Regency - Prima, Empiri Tahya; Cahyono, Agus; Jazuli, Muhammad (Catharsis, 2020)
Tandhakan Wedok Dance grows and develops in the Jatiguwi Village environment. This dance has already existed since 1930 and it does not know who its creator. However, the Tandhakan Wedok Dance was inactive in 1932-1990. Around 1990 the Tandhakan Wedok Dance was just remade by Mbah Madyo and Mbah Chatam. The purpose of this study is to describe, analyze, and interpret narratively about a revitalization of Tandhakan Wedok Dance by using an anthropological dance approach. This study is focused on the Tandhakan Wedok Dance, including the revitalization of the Tandhakan Wedok Dance with the research location of Jatiguwi Village, Sumberpucung District, Malang Regency. The techniques used for the data collection in this study are observation, interviews, and documentation. The results of the research are as follows: the stages of the revitalization process which consists of reformulating new views, communication, organization, adaptation, cultural transformation, and routines. The Tandhakan Wedok Dance presentation consists of movement, music accompaniment, make-up and clothing, and floor patterns. The Tandhakan Wedhok Dance movements are divided into elements of motion which are divided into four, consisting of elements of the head, hands, body, and feet. The motion motives consist of 25 motives of motion. The motion phases are divided into 20 phrases. Sentences of motion/ types of movements of the Tandhakan Wedok Dance namely stationary motion, various motor movements, and various connecting motion. Paragraphs or motion groups have three groups, namely gawang forward, core, gawang backward. 15 musical instruments used in the Tandhakan Wedok Dance. The makeup used is beautiful makeup and for fashion, namely cundhuk penthul, sunggar, jasmine flower, suweng, necklace, long cloth for dodotan, belt, sampur/ shawl, and jarik. There are nine floor patterns of the Tandhakan Wedhok dance.